The Challenges of Implementing Online-Based Leadership in The Application of Education Innovations - Masrur Masrur (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The purpose of this study was to find out the challenges of online-based leadership implementation in post-pandemic educational innovation applications at Public Aliyah Madrasah (MAN). This study uses a qualitative approach with purposive and snowball sampling techniques. The findings show that: The challenge in improving the quality and competitiveness of online-based schools after the pandemic is the need to develop superior human resources to prepare the community and nation to face the knowledge age as a competitive era. The challenge in Human Resources (HR) and online-based finance after the pandemic is to build a new structure that improves teacher coordination and collaboration that utilizes the expertise of all educators, ultimately leading to better working conditions and workplaces; As for the challenges in improving the quality of online-based leadership post-pandemic, namely leadership that is disruptive to the current progress and creative in terms of policies which include the stages of preparation, enlightenment, elaboration, and verification.